Control for PEM fuel cell - Chen, Chao. (2010)
With increasing demand in energy, concern in resource depletion and worry for environmental issues, it is important for us to find out clean and renewable energies to solve the above issues so that satisfy the need of human being and maintain the sustainability of ecology system for the future generation. Among various energy options such as solar energy, wind energy, and nuclear energy etc, PEM Fuel Cell being the potential candidate is under great research and development. Due to its environmental friendly with zero pollutant emission, high energy efficiency and quite performance, there are lots of further investigations and applications in the portable, transportation and stationary sectors.